Thermal runaway evaluation using DSC1, VSP2, and kinetics models on Cu etchant and its waste in high-tech etching process - Lin, Yu-Jung; Lin, Zih-Syuan; Wang, Yih-Wen (Journal of thermal analysis and calorimetry, 2021)
Cu etchant solutions have been widely used in etching processes because of their high etching efficiency and low cost for manufacturing electric products. Hydrogen peroxide (H 2 O 2 ), a major components of Cu etchants, is known for its instability and reactivity under thermal induction, metal-ion catalysis, or pyrolysis; thus, Cu etchants have a higher risk of thermal explosion than other etchant solutions do. In this study, the exothermic reaction of the Cu etchant was initiated at approximately 70 °C, and the exothermic enthalpy (Δ H ) of the first peak was measured to be approximately 274.4 J g −1 using differential scanning calorimetry 1 (DSC1). The American Society for Testing and Materials (ASTM)—Ozawa/Kissinger method, and Advanced Kinetics and Technology Solutions (AKTS)—Friedman simulation, were used to calculate the reaction kinetics. Thermal runaway and gas evolution were evaluated through vent sizing package 2 (VSP2). The pressure of the Cu etchant surged from atmospheric pressure to a maximum pressure of 225.075 psig, with a pressure increase of 168.684 psig min −1 in the VSP 2 adiabatic test. Finally, to improve the safety operation during the etching process, thermokinetic analysis was used to identify appropriate kinetic parameters for the thermal decomposition of the Cu etchant.